PENEGAKAN HUKUM TINDAK PIDANA PENCABULAN TERHADAP ANAK DIBAWAH UMUR MENURUT UU NO. 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UU NO. 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Syaiful Ahmad Dinar (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
The crime of sexual abuse of minors is not something that can be considered a small and unimportant problem. This problem is very important, the victims are minors, where children as the nation's buds and the next generation of the nation's ideals must be considered, protected and guarded from all actions that can harm them. Therefore, not only his family plays an active role but all levels of society play an active role in paying attention, protecting, and protecting him. The type of research used by the author is qualitative research, namely the author conducts research with the intention of being able to understand the phenomenon of what is experienced by the object or research subject. In this study, to find out the information contained in books, as well as articles related to existing problems. In the study used by the author is a normative study (Library Research). In this paper, it can be concluded that the enforcement of criminal law in cases of criminal acts of obscenity is regulated in the child protection law article 17 paragraph 2 which states that